The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1136/adc.2004.049502
|View full text |Cite
|
Sign up to set email alerts
|

Minor illness and injury: factors influencing attendance at a paediatric accident and emergency department

Abstract: Aims: To gather information on children with minor illness or injury presenting to a paediatric accident and emergency (A&E) department and the decision making process leading to their attendance. Methods: Prospective questionnaire based survey of 465 children selected by systematic sampling from A&E attenders allocated to the lowest triage category. Results: The study population was statistically representative of the total population of A&E attenders. The lower deprivation categories were over represented. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 24 publications
(19 reference statements)
8
63
0
2
Order By: Relevance
“…In this study, the population proportion of young children (<5 years), was associated with A&E rates, as found in some other studies, 9,28 but the population proportion of older adults (>65, >75, or >85 years) had no significant association. This contrasts with the findings of some studies, 24 but supports others.…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
See 3 more Smart Citations
“…In this study, the population proportion of young children (<5 years), was associated with A&E rates, as found in some other studies, 9,28 but the population proportion of older adults (>65, >75, or >85 years) had no significant association. This contrasts with the findings of some studies, 24 but supports others.…”
Section: Comparison With Existing Literaturesupporting
confidence: 63%
“…This contrasts with the findings of some studies, 24 but supports others. 9,28 The present study found that the two included ethnic groups were associated with opposite effects on A&E attendance: higher proportions of Asian or Asian British patients were associated with lower A&E attendance rates whereas higher proportions of black or black British patients were associated with higher rates. Earlier studies had shown that white groups used A&E more than those from non-white backgrounds, [11][12][13] although the studies were based on relatively small geographical areas with high proportions of particular non-white ethnic groups and therefore with limited generalisability to other areas of the UK.…”
Section: Comparison With Existing Literaturementioning
confidence: 71%
See 2 more Smart Citations
“…We know that parents' choice of utilisation is determined by the availability of care, socio-economic factors (Shipman et al, 1997) and their own health beliefs (Hendry et al, 2005). Qualitative research is needed to improve our understanding of parental decision making when choosing which primary care service provider to attend for their children's presenting symptom.…”
Section: Further Researchmentioning
confidence: 99%